TiO2 nanotubes supported Cu nanoparticles for improving photocatalytic degradation of simazine under UV illumination - Meriam Suhaimy, Syazwan Hanani; Abd Hamid, Sharifah Bee; Chin, Wei Lai; Hasan, Md. Rakibul; Johan, Mohd Rafie (Multidisciplinary Digital Publishing Institute (MDPI), 2016)
Nano size Copper (Cu) incorporated TiO2 nanotubes was successfully synthesized via the anodic oxidation technique in ethylene glycol (EG) containing 0.5 wt % NH4F and 1.6 wt % KOH for the photocatalytic degradation of Simazine (2-chloro-4, 6-diethylamino-1,3,5-triazine) under Ultraviolet (UV) illumination. In the present study, the influence of different loading Cu concentrations on the formation of Cu-TiO2 nanotubes film towards the photocatalytic degradation of Simazine is reported. Based on our study, it was found that the optimum Cu loading concentration was about 0.45 wt % on TiO2 nanotubes film for approximately 64% photocatalytic degradation of Simazine after 4 h under UV illumination. This finding was mainly attributed to the uniform surface covering of the Cu loaded TiO2NTs which acted as electron traps, preventing the recombination of electron hole pairs, eventually leading to higher photocatalytic activity of our photocatalyst in degrading the targeted organic pollutant, Simazine. Moreover, an increased kinetic rate of the degradation to 0.0135 h−1 was observed in the presence of Cu in TiO2NTs.